High Hydrostatic Pressure-Assisted Extraction of High-Molecular-Weight Melanoidins from Black Garlic: Composition, Structure, and Bioactive Properties - Yimeng Zhao; Yongli Jiang; Yanfang Ding; Danfeng Wang; Yun Deng (Journal of Food Quality)
Melanoidin is one of the most important ingredients in black garlic due to the high nutritional values and biological functions. High hydrostatic pressures from 200 to 500 MPa were employed to extract the melanoidins from black garlic for improving the extraction efficiency and enhancing the activities. The results indicated that total phenolics, flavonoids, and sugar yields were all increased when pressure was applied and the antioxidant and overall reducing power was maximized. The bioactive properties of protein tyrosine phosphatase 1B, angiotensin-converting enzyme, and trypsin inhibitory activities were also enhanced compared with the control. Moreover, FT-IR spectroscopy indicated high pressure altered the melanoidin structures to different degrees. It was found that an application of 300 MPa for 5 min was the optimal treatment protocol under all operating conditions.